2010
DOI: 10.1037/a0021742
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mindfulness and examining its relationship with alcohol use and negative consequences.

Abstract: Mindfulness has been proposed as a useful adjunct to alcohol abuse treatment. However, very little research has examined the basic relationship between alcohol use and mindfulness. Inconsistency in definition and measurement of mindfulness across studies makes research difficult to interpret and conduct. Therefore, the current research sought to validate an emerging mindfulness measure, the Five Facet Mindfulness Questionnaire (FFMQ), and examine its relationship with alcohol use and alcohol-related negative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
104
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 59 publications
15
104
2
4
Order By: Relevance
“…Future studies might consider using stratified sampling procedures to obtain a more diverse range of participants' relationship functioning, sexual satisfaction, and trait mindfulness. Finally, future studies might consider examining additional variables that have been shown to be associated with individuals' levels of trait mindfulness (e.g., alcohol use; Fernandez, Wood, Stein, & Rossi, 2010), as these variables might influence or mediate the effects of mindfulness on dating partners' relational outcomes. Despite these limitations, the current study provides the first empirical exploratory examination of how the five facets of mindfulness are differentially associated with relationship satisfaction and sexual satisfaction in dating relationships, and suggest that increased sexual satisfaction may be one mechanism through which they contribute to relationship satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…Future studies might consider using stratified sampling procedures to obtain a more diverse range of participants' relationship functioning, sexual satisfaction, and trait mindfulness. Finally, future studies might consider examining additional variables that have been shown to be associated with individuals' levels of trait mindfulness (e.g., alcohol use; Fernandez, Wood, Stein, & Rossi, 2010), as these variables might influence or mediate the effects of mindfulness on dating partners' relational outcomes. Despite these limitations, the current study provides the first empirical exploratory examination of how the five facets of mindfulness are differentially associated with relationship satisfaction and sexual satisfaction in dating relationships, and suggest that increased sexual satisfaction may be one mechanism through which they contribute to relationship satisfaction.…”
Section: Discussionmentioning
confidence: 98%
“…Research has demonstrated that these facets are unique and certain facets are more strongly associated with specific outcomes. The act with awareness and nonreactivity facets, both characterized by automatic and emotionally-driven behavior, are more strongly associated with destructive behaviors such as alcohol use and impulsivity (Fernandez, Wood, Stein, & Rossi, 2010; Peters, Erisman, Upton, Baer, & Roemer, 2011), whereas the nonjudging facet has been shown to be associated with decreased rumination (Lykins & Baer, 2009). …”
Section: Mindfulnessmentioning
confidence: 99%
“…This could account for the overall small relationship between trait mindfulness and substance use behaviors found in prior studies. Indeed, the five facets of mindfulness have been shown to be differentially related with substance use behaviors—with acting with awareness, non-judgment, and non-reactivity being the facets most frequently related to reduced substance use behaviors (Bodenlos et al, 2013; Fernandez et al, 2010; Leigh and Neighbors, 2009; Murphy and MacKillop, 2012). Additionally, trait mindfulness might be differentially related to distinct substance use behaviors (Black et al, 2011; Fernandez et al, 2010; Robinson, 2010).…”
Section: Introductionmentioning
confidence: 99%